Chili Picker Tool - Muhammad Adam Sufi Mohd Safri,; Muhammad Aiman Haqimie Mohd Jamil,; Muhammad Adib Akmal Mohd Hafiz,; Othman, Khairulnizam (Multidisciplinary Applied Research and Innovation, 2024)
This paper presents the design and development of a chili picker tool aimed at revolutionizing the chili harvesting process. The tool improves efficiency, productivity, and reduces manual labor in agriculture. Materials and machines used in creating the tool are carefully selected for quality and functionality. Inspired by the mechanism of a hair clipper, the chili picker tool incorporates a horizontally moving blade to break the chili's pedicle. This mimics the way farmers pluck chilies with their thumbs, which also move horizontally. To determine the optimal force required to break the pedicle, the study investigates the characteristics of bird's eye chilies. An equation is derived to calculate the power produced by the DC motor, enabling determination of the cutting force needed. Experimental results show comparable performance to conventional methods, with suggestions for improving motor speed and torque. The chili picker tool has significant potential impact. By reducing reliance on manual labor, it offers a more efficient and productive alternative to traditional harvesting methods. This innovation addresses the labor-intensive nature of chili farming, minimizes crop damage, and boosts profitability for farmers. It also preserves the chili plant, allowing for continued growth and potential increased yields. The fresher and better-conditioned chilies harvested with the tool may fetch higher prices in the market. In conclusion, the chili picker tool has the potential to transform chili harvesting by providing a more efficient, productive, and sustainable alternative to manual labor. Further improvements are suggested, but this tool offers a realistic option to optimize chili farming, increase profitability, and meet culinary industry demands.